2019
DOI: 10.1002/hipo.23093
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of gamma‐frequency oscillation by feedforward inhibition: A computational modeling study

Abstract: Throughout the brain, reciprocally connected excitatory and inhibitory neurons interact to produce gamma‐frequency oscillations. The emergent gamma rhythm synchronizes local neural activity and helps to select which cells should fire in each cycle. We previously found that such excitation‐inhibition microcircuits, however, have a potentially significant caveat: the frequency of the gamma oscillation and the level of selection (i.e., the percentage of cells that are allowed to fire) vary with the magnitude of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 94 publications
(126 reference statements)
0
12
0
Order By: Relevance
“…In the granular layer of the cerebellar cortex, previous studies have indicated that neural oscillations relate to the feedback loop between GoCs and GCs [ 19 , 30 , 35 , 53 ]. Moreover, oscillations can be modulated by the balance of excitation and inhibition [ 33 , 34 ] and feedforward inhibition [ 31 , 32 ]. Consistent with these findings, our results indicate that feedback inhibition is crucial for generating oscillation that can be further modulated by the balance of excitation and inhibition inputs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the granular layer of the cerebellar cortex, previous studies have indicated that neural oscillations relate to the feedback loop between GoCs and GCs [ 19 , 30 , 35 , 53 ]. Moreover, oscillations can be modulated by the balance of excitation and inhibition [ 33 , 34 ] and feedforward inhibition [ 31 , 32 ]. Consistent with these findings, our results indicate that feedback inhibition is crucial for generating oscillation that can be further modulated by the balance of excitation and inhibition inputs.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been proposed for synchronous firing, including feedforward inhibition from inhibitory neurons to excitatory neurons [9,19,20], feedback inhibition where excitation dominates inhibition [21], opposite bursting patterns of excitatory and inhibitory neurons [22][23][24][25], and gap junctions between inhibitory neurons [26][27][28][29][30]. Furthermore, oscillations can also be modulated by the balance of excitation and inhibition in cells [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…This circuit function has been termed “winner-take-all,” or “lateral” inhibition, whereby the neurons receiving the highest level of excitatory input recruit feedback inhibition that suppresses neighboring neurons which are receiving less excitation. However, previous modeling work has shown that feedback inhibition alone is not able to prevent the number of active output neurons from increasing as the total amount of afferent input grows (Rennó-Costa et al, 2019 ). Furthermore, it is not clear if the extremely low fraction of active output neurons in circuits with ultrasparse representations like the hippocampal dentate gyrus is sufficient to activate the level of feedback inhibition necessary to support “winner-take-all” competition.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition from interneurons that receive the same incoming afferent inputs as the output neurons is termed “feedforward inhibition," and inhibition from cells that receive input from the output neurons themselves is called “feedback inhibition.” These classes of interneurons have been implicated in specific computational functions in neural circuits. One important function proposed for feedforward inhibition is “background subtraction,” whereby inhibition grows in proportion to and cancels the average level of input to the circuit, enabling only large fluctuations in inputs above the average level to drive circuit output (Grienberger et al, 2017 ; Rennó-Costa et al, 2019 ). Here we ask whether this background subtraction mechanism can support a constant level of output given a wide range in the total number of active inputs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation